Knowledge, attitude and practice of Nepali medical and dental practitioners on infection control during Covid-19 Pandemic (Orthodontic Journal of Nepal, 2020)
Introduction: Coronavirus Disease 2019 (COVID-19) has been declared a global public health emergency which is affecting people across the world. Health care professionals and their working environment are in close by vicinity to the patient. The chance of cross-contamination and spread of infection is high if proper infection control measures are not taken. Hence, the aim of this study was to assess the knowledge, attitude and practice (KAP) of Nepali medical and dental practitioners on infection control during the COVID-2019 pandemic.Materials and Method: A self administered questionnaire was formulated and circulated online among health care practitioners. Questionnaire consisted of questions on knowledge, attitude and practice regarding infection control on COVID-19 pandemic. A scoring criteria was set, giving score 1 to the correct answer and score 0 to the incorrect answer. Total scores were calculated and levels of knowledge, attitude and practice were assessed. Mean scores for medical and dental practitioners were also assessed and compared.Result: Total 80% of the total participants had not received training on infection prevention and control practices specifically for COVID-19. Only 19.3%, 4.7%, 9.5% participants scored maximum scores for knowledge, attitude and practice, respectively. Majority of the participants (around 80%) had good attitude towards infection control regarding COVID-19 pandemic.Conclusion: There is a need for specific training on infection prevention and control on COVID-19 for Nepali health care professionals. Supply of personal protective equipment materials required for infection control against COVID-19 in health care facility should improve to combat against this pandemic.